Effect of composition on magnetocaloric properties of Mn3Ga(1-x)SnxC - Dias, E. T.; Priolkar, K. R.; Cakir, O.; Acet, M.; Nigam, A. K. (AMER INST PHYSICS, 2015)
A study investigating the effect of Sn substitution on the magnetocaloric properties of Mn3Ga(1-x)SnxC compounds reveals that the nature of the magnetocaloric effect (MCE) has a strong dependence on the nature of the magnetic ordering. For small amounts of Sn (x = 0.71) results in a change of the MCE to a conventional type with very little variation in the position of (Delta S-M)(max) with increasing magnetic field. This has been explained to be due to the introduction of local strain by A site ions (Ga/Sn), which affect the magnetostructural coupling in these compounds. (C) 2015 AIP Publishing LLC.
Keywords: MAGNETIC ENTROPY CHANGE; ROOM-TEMPERATURE; FERROMAGNETIC TRANSITION; MN3GAC; REFRIGERATION; PEROVSKITES; MANGANESE; Physics